Medorrhinum - Mercaldo, Mauro (British Homeopathic Journal, 1996)
A review of the provenance, key symptoms and clinical uses of Medorrhinum. Listing of the drug in Kent's Repertory is discussed.
Keywords: Medorrhinum; Gonorrhoea; Inherited sycotic taint; Asthma; Condyloma acuminata; Mind; Mental or psychic disorders; Oligomenorrhoea; Migraine; Mammary dysplasia